2022
DOI: 10.1242/dev.200984
|View full text |Cite
|
Sign up to set email alerts
|

The GATA factor ELT-3 specifies endoderm in Caenorhabditis angaria in an ancestral gene network

Abstract: Endoderm specification in C. elegans occurs through a network in which maternally provided SKN-1/Nrf, with additional input from POP-1/TCF, activates the GATA factor cascade MED-1,2→END-1,3→ELT-2,7. Orthologues of the MED, END, and ELT-7 factors are found only among nematodes closely related to C. elegans, raising the question of how gut is specified in their absence in more distant species in the genus. We find that the C. angaria, C. portoensis and C. monodelphis orthologues of the elt-3 GATA factor gene are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(27 citation statements)
references
References 95 publications
2
24
1
Order By: Relevance
“…This pattern overlaps that of end-3 and end-1 together, suggesting that ELT-3 fulfills the roles of these factors in C. angaria [ 51 , 52 , 74 ]. Consistent with this, RNAi or a null mutation in Can-elt-3 resulted in penetrant loss of gut with a phenotype resembling C. elegans end-1,3 double mutants [ 9 , 16 ].…”
Section: Gut Specification Outside Of the Elegans Supergroup By The E...mentioning
confidence: 71%
See 4 more Smart Citations
“…This pattern overlaps that of end-3 and end-1 together, suggesting that ELT-3 fulfills the roles of these factors in C. angaria [ 51 , 52 , 74 ]. Consistent with this, RNAi or a null mutation in Can-elt-3 resulted in penetrant loss of gut with a phenotype resembling C. elegans end-1,3 double mutants [ 9 , 16 ].…”
Section: Gut Specification Outside Of the Elegans Supergroup By The E...mentioning
confidence: 71%
“…Our recent work in the species C. angaria , which lies outside of the Elegans supergroup, revealed that the upstream portion of gut specification in this species consists not of a multifactor GATA cascade but merely of the single GATA factor ELT-3 [ 9 ]. In this study, we showed that a C. angaria elt-2 translational reporter gene is expressed similarly to C. elegans elt-2 when introduced into C. elegans as a transgene.…”
Section: Gut Specification Outside Of the Elegans Supergroup By The E...mentioning
confidence: 99%
See 3 more Smart Citations